(untitled) (Scientific journal of the Fergana State University, 2023)
This article draws attention to the fact that the activities organized in connection with the education of tolerance in future foreign language teachers include various directions of tolerance, on the one hand, the knowledge provided within the existing socio-political, philosophical views of the science of priority tasks.